Super thermoplastic vulcanizates based on carboxylated acrylonitrile butadiene rubber (XNBR) and polyamide (PA12). (May 2016) - Chatterjee, T.; Basu, D.; Das, A.; Wiessner, S.; Naskar, K.; Heinrich, G.
Graphical abstract: Highlights: Super TPV based on XNBR and PA12 via the application of novel cyclic peroxide. Highest mechanical properties and thermal stability of TPV of 50:50 XNBR-PA12. Superior performance behaviour with reference to heat and oil aging study. Abstract: Thermoplastic vulcanizates (TPVs) are special classes of thermoplastic elastomers, in which dynamic vulcanization of the rubber phase takes place during melt mixing with a semi-crystalline thermoplastic matrix phase at elevated temperature. TPV is characterized by processing behaviour like thermoplastic at elevated temperature and performance properties of vulcanized rubber at ambient temperature. High performance TPVs or super TPVs are new generation TPVs which exhibit high heat resistance as well as excellent oil resistance property suitable for automotive under-the-hood applications. In the present work, a new super TPV based on carboxylated acrylonitrile butadiene rubber (XNBR) and polyamide (PA12) has been developed. (XNBR:PA12) TPVs of different blend ratios have been prepared by using a fixed concentration of novel cyclic monofunctional peroxide. Final morphology of TPVs varies from either a co-continuous to a dispersed one depending on the blend ratio. TPV of 50:50 XNBR-PA12 shows the highest mechanical properties as well as superior thermal stability among all other TPVs. From differential scanning calorimetric (DSC) study, it can be clearly seen that the glass transition temperature (Tg ) of XNBR has shifted to high temperature range in case of all TPVs as compared to that of uncrosslinked blend system. Dynamic mechanical analysis (DMA) also demonstrates that tan δ values of all the TPVs are lower and the storage moduli are higher than the uncrosslinked blend system. Lowest tan δ peak of TPV of 50:50 blend ratio of XNBR:PA12 indicates the highest degree of crosslinking and this is also supported by the swelling studies. The highest level of mechanical properties and superior thermal stability support that phenomenon. Heat aging and oil resistance study have also been carried out in details to understand the performance behaviour of these super TPVs at service condition.